Nurses’ perspective on the management of adverse events in primary healthcare clinics - W.B. Zondi, T. M. Khoza (Opción, 2019)
The main aim of the study was to explore the reasons why nurses fail to implement the available laid down procedures of dealing with adverse events. The quantitative research methodology was applied to reach the purposes of the study. The authors found that as much as nurses are orientated on the policy of adverse events management, there is no ongoing training on the management of adverse events. Furthermore, the study found that staff is not included in the planning on the management of adverse events and the adverse events management committees are not fully representative of all categories of staff.